Valve morphology of Diploneis sudamericana nov. sp.and Diploneis elliptica (Kützing) Cleve - Sala S.E. Vouilloud A.A. Heguilor S. (Nova Hedwigia, 2018)
Diploneis Ehrenberg ex Cleve is a diverse genus, with species predominantly from epipelic, marine habitats; there are a few freshwater representatives. In 1933 Frenguelli reported four taxa of this genus at the Esteros del Iberá, a vast subtropical wetland from Argentina. Two of the four taxa reported were new for science. One of the reported species was Diploneis elliptica (Kützing) Cleve (Basionym: Navicula elliptica Kützing) a species cited from very diverse environments of every continent. In this study the type material of Navicula elliptica Kützing, deposited at the Natural History Museum in London, was analyzed with scanning electron microscopy and its valve fi ne structure described. Comparison of this type material with others studied under SEM from America, Europe, Africa and Asia indicate that D. elliptica has been widely misidentifi ed. The materials from Iberá, Argentina, deposited under this name in the Frenguelli´s Collection at the Museo de Ciencias Naturales de La Plata, belong to a new species, described here as Diploneis sudamericana. These two taxa are very similar when analyzed with LM but clearly diff er in the striae and areolae structure. D. sudamericana has uniseriate striae at valve center and biseriate near the valve margin; the alveoli are externally occluded by a unique complex cribrate occlusion. This species also diff ers from others in the areolae of the longitudinal canals and the external proximal raphe ends.